Pengaruh Iklim Organisasi dan Stres Kerja terhadap Turnover Intention pada Karyawan CV. HD Citarasa - Nida Nurul Amalia; Chandra Fitra Arifianto (PT. PENERBIT TIGA MUTIARA, 2024)
This research aims to examine both partially and simultaneously the influence of Organizational Climate and Job Stress on Turnover Intention at CV. HD Citarasa of South Tangerang. The research method used is descriptive quantitative which is verification in nature. The respondents used were all employees CV. HD Citarasa South Tangerang has 56 employees. The data analysis techniques used include validity instrument analysis, reliability instrument analysis, and hypothesis testing both partially and simultaneously using the Statistical Package for Social Science (SPSS) for Windows version 26 program. The partial research results show that Organizational Climate has a positive influence on Turnover Intention obtained tcount (3.288) > ttable (1.674). Then, Job Stress has a positive influence on Turnover Intention, the value obtained is tcount (5.070) > ttable (1.674). As for the simultaneous results, it shows that Organizational Climate and Work Stress have a positive influence on Turnover Intention with the hypothesis results (simultaneously) obtaining a value of fcount (16.512) > ftable (3.172).